Being and the Mystic: the metaphysical foundations of Thomas Aquinas' mystical thought - Erb, Heather M. (Verbum – Analecta Neolatina, 2004)
Various mystical traditions and much of modern scholarship sever the connection between mysticism and metaphysical claims. For Aquinas, differing ontological claims both generate and correlate logically to diverse mystical claims, under the aegis of one analogous notion of truth. In this way, Aquinas' mystical theology offers a metaphysics of mystical union, according to which a thing's nobility of being corresponds to its degree of union with God. Aquinas' metaphysical positions both define and circumscribe his interpretation of religious experience. This examines the points of contact between metaphysics andmysticism. Second, it takes the metaphysical issue of monism versus pluralism as a locus for intersecting truth claims in metaphysics and mysticism. Third, examines the context, formulation and solution to the problem of the "one and the many" within Aquinas' metaphysics, including its relevance for his mystical theology. Fourth, it examines a metaphysical paradox taken from the domain of the intellect, and show how it stands at the threshold of mystical experience for Aquinas.